2008
DOI: 10.1590/s1519-566x2008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodism and seasonality in neotropical population of Plutella xylostella L. (Lepidoptera: Yponomeutidae)

Abstract: Fotoperiodismo e Sazonalidade em População Neotropical de Plutella xylostella L. (Lepidoptera:Yponomeutidae)RESUMO -Populações neotropicais de Plutella xylostella L. possuem ciclos sazonais de crescimento e declíneo e a migração é um fator-chave na geração da dinâmica populacional. Devido à previsibilidade sazonal das oscilações populacionais, o fotoperíodo poderia agir como o sinal que desencadea o comportamento migratório do inseto. Migrações de insetos são geralmente precedidas por diapausa reprodutiva, uma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…The effect of different canola cultivars on developmental time and adult longevity of P. xylostella (Tables 2 and 3) were similar to those reported for P. xylostella on canola (Ebrahimi et al 2008, Golizadeh et al 2009), cabbage (Campos 2008), and some Brassica vegetables (Syed and Abro 2003) in previous studies. Our developmental time data were much lower than those reported for P. xylostella on cabbage (28.84 Ϯ 1.85 d) (Ahmad et al 2008).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The effect of different canola cultivars on developmental time and adult longevity of P. xylostella (Tables 2 and 3) were similar to those reported for P. xylostella on canola (Ebrahimi et al 2008, Golizadeh et al 2009), cabbage (Campos 2008), and some Brassica vegetables (Syed and Abro 2003) in previous studies. Our developmental time data were much lower than those reported for P. xylostella on cabbage (28.84 Ϯ 1.85 d) (Ahmad et al 2008).…”
Section: Resultssupporting
confidence: 87%
“…Highest peak in each graph reveal the early stage cause-speciÞc mortality (d x is part of original cohort dying between two consecutive days). study were greater than those reported by Campos (2008) for cabbage (4.4 d) and was similar to those reported by Golizadeh et al (2009) on canola PF under the same environmental conditions (male longevity, 6.40; female longevity, 8.33 d), by Ahmad et al (2008) for cabbage (8.46 d), and these differences can be attributed to host plant type, although different geographical region may be a signiÞcant factor.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Atwal (1955) and Shirai (1993) found that larval development was slower under shorter (9:15 hours, (Atwal, 1955;Campos, 2008). Although studies in the past have demonstrated extended development time and decreased fecundity as a result of photoperiod, Campos (2008) proposed that indirect effects of photoperiod is the likeliest explanation for these observations. In addition, there is the potential for the effects to be population dependent; the effects of photoperiod should be revisited in the context of temperate and tropical populations as well as, overwintering.…”
Section: Photoperiodmentioning
confidence: 99%
“…The consensus in the literature is that the diamondback moth does not overwinter in diapause (Hardy, 1938;Frost, 1949;Atwal, 1955;Harcourt and Cass, 1966;Butts, 1979;Smith and Sears, 1982;Kimura et al, 1987a;Saito, 1994b;Campos, 2008;Kim et al, 2015); instead it likely survives unfavourable conditions in a state of quiescence Campos, 2008). This is demonstrated by: (1) the slowing of development in response to decreasing temperature with no indication of arrested development (Atwal, 1955;Liu et al, 2002); (2) the ability to become active immediately when placed back in favourable conditions despite long durations at 0…”
Section: Overwintering Strategymentioning
confidence: 99%